2012
DOI: 10.1038/cdd.2012.95
|View full text |Cite
|
Sign up to set email alerts
|

Optic atrophy 1 mediates mitochondria remodeling and dopaminergic neurodegeneration linked to complex I deficiency

Abstract: Mitochondrial complex I dysfunction has long been associated with Parkinson's disease (PD). Recent evidence suggests that mitochondrial involvement in PD may extend beyond a sole respiratory deficit and also include perturbations in mitochondrial fusion/fission or ultrastructure. Whether and how alterations in mitochondrial dynamics may relate to the known complex I defects in PD is unclear. Optic atrophy 1 (OPA1), a dynamin-related GTPase of the inner mitochondrial membrane, participates in mitochondrial fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 43 publications
3
51
0
Order By: Relevance
“…Reduced NADH:ubiquinone oxidoreductases (also called complex I) and/or increased NADPH oxidase leads to oxidative stress [18]. A previous study showed that mitochondrial Opa1 reduction induced complex I deficiency through the disruption of mitochondrial morphology, leading to the accumulation of mitochondrial ROS [27]. Herein we identified Opa1 as a downstream effector of Tom70, and Tom70 reduction caused the significant downregulation of complex I activity (Supplementary information, Table S1 and Figure S7).…”
Section: Discussionmentioning
confidence: 58%
“…Reduced NADH:ubiquinone oxidoreductases (also called complex I) and/or increased NADPH oxidase leads to oxidative stress [18]. A previous study showed that mitochondrial Opa1 reduction induced complex I deficiency through the disruption of mitochondrial morphology, leading to the accumulation of mitochondrial ROS [27]. Herein we identified Opa1 as a downstream effector of Tom70, and Tom70 reduction caused the significant downregulation of complex I activity (Supplementary information, Table S1 and Figure S7).…”
Section: Discussionmentioning
confidence: 58%
“…In mammals, OPA1, a substrate of i-AAA, controls crista remodeling and mediates apoptotic neurodegeneration. 58,59 However, the S2 cleavage site of i-AAA is not present in Drosophila OPA1. 60 Ectopic overexpression of another mitochondrial protease, Rhomboid-7, could process dOPA1.…”
Section: Discussionmentioning
confidence: 99%
“…24 Therefore, while LMP is detected earlier than MOMP following MPTP/MPP + treatment, MOMP seems to occur independently of LMP in this pathological situation. However, we cannot completely exclude the possibility of LMP and MOMP affecting each other in this model.…”
Section: Bax Translocates To Lysosomal Membranes Early Following Mptpmentioning
confidence: 99%
“…[21][22][23] It was previously shown that BAX permeabilizes mitochondrial membranes in this experimental model and plays an instrumental role in MPTP-induced dopaminergic cell death. 10,11,13,21,24 Here, we assessed whether BAX may also be responsible for LMP and subsequent lysosomal deficiency occurring in this model of PD. To this purpose, we determined the presence of BAX by immunoblot in pure (mitochondria-free) lysosomal fractions isolated from the ventral midbrain region (which contains the SNpc) of saline-and MPTP-treated mice.…”
Section: Bax Translocates To Lysosomal Membranes Early Following Mptpmentioning
confidence: 99%